Biblioteca virtual temática em saúde: interatividade com usuário leigo - Lourenço, Regina Goulart (2013)
This study presents and analyzes the behavior of layman users, embedded in socioeconomic class C, in the search for health information in the virtual library. This is a literature research and exploratory study to know the potential of interactivity and communication between virtual library and user. The health area was used to cater for the study. Concepts of information, knowledge, virtual library, user behavior, marketing and health promotion are presented. In the research field a set of instruments was used for the gathering of data that included semi-structured interview, questions to characterize the respondent, and the technique of thinking aloud. The results indicated difficulties, barriers and expectations of users in relation to the searches performed in the virtual library. Suggestions are made to expand the interaction between user and virtual library